ANALISIS MAKNA HURUN ‘IN DALAM AL-QUR’AN (KAJIAN TEORI SEMIOTIKA ROLAND BARTHES) - Malia, Hayuni; Atmi, Syifaun Nufus (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2023)
AbstractGenerally, the meaning of the word hurun ‘in as an expression for angel is limited to the denotation meaning, so it tends to be sensual, matrealistic and discriminatory that refers to one gender. Therefore, the purpose of this research is to reveal the connotative (broader) meaning of angels expressed by the word hurun ‘in. This research use Roland Barthes’ semiotic theory as an analytical tool to review the concept of angels in the Qur’an. in order to find the full meaning of the word hurun ‘in. The Result of the research, the hidden (connotative) meaning of the word hurun ‘in in the Qur’an was discovered. The Qur’an does not mention angels limited to a female figure who has absolute beauty. Angels are not only created for male believers. However, it is also intended for female believers, as an imbalance for the provisions they prepare when in the world. Allah made angels as a sign of love for servants who are faithful to maintain the perfection of love for Him, who always enrich their faith, and strengthen their devotion to Allah SWT. Therefore, the interpretation of hurun ‘in cannot be limited to the literal meaning, a deeper exploration is needed to reveal the true meaning, so that gender bias does not occur.Keywords: Al-Qur’an; Hurun ‘in, Roland Barthes. AbstrakUmumnya pemaknaan terhadap kata hurun ‘in sebagai ungkapan untuk bidadari sebatas pada makna denotasi, sehingga cenderung sensual, bersifat matrealistis dan diskriminatif yang mengacu pada salah satu gender. Atas dasar itu, tujuan dari penelitian ini adalah untuk mengungkap makna yang konotatif (yang lebih luas) dari bidadari yang diungkapkan dengan kata hurun ‘in. Penelitian ini menggunakan teori semiotika Roland Bartehs sebagai pisau analisis untuk meninjau kembali konsep bidadari dalam al-Qur’an, dalam rangka pencarian makna yang utuh terkait kata hurun in. Hasil penelitian, ditemukan makna yang tersembunyi (konotatif) dari kata hurun ‘in dalam al-Qur’an. Al-Qur’an tidak menegaskan bidadari terbatas pada sosok perempuan pemilik kecantikan yang mutlak, bidadari tidak hanya diciptakan untuk laki-laki mukmin. Akan tetapi, juga diperuntukkan bagi perempuan beriman, sebagai sebuah imbalan atas bekal yang mereka persiapkan ketika di dunia. Allah menjadikan bidadari sebagai tanda kasih bagi hamba-hamba yang istiqamah menjaga keindahan cinta kepadaNya, yang senantiasa memperindah iman, dan meningkatkan ketaqwaan kepada Allah SWT. Oleh karenanya, pemaknaan terhadap hurun ‘in tidak bisa hanya sebatas pada makna literal, diperlukan penelusuran lebih mendalam untuk mengungkap makna yang sebenarnya, agar tidak terjadi bias gender. Kata Kunci: Al-Qur’an; Hurun ‘in, Roland Barthes.